The American genera of Asilidae (Diptera): keys for identification with an atlas of female Spermathecae and other morphological details. IX.6. subfamily Asilinae leach - Mallophora -group, with a catalogue of the neotropical species - Artigas, Jorge N.; Papayero, Nelson (Arquivos de Zoologia, 1997)
A key is given for the identification of the 6 American genera of the Mallophora-group of Asilinae (Asilidae), with illustrations of female spermathecae and other morphological details. A catalogue of the neotropical species is included.